Prediction of the catalytic site of single-atom Ni catalyst using the hydrogen evolution reaction as a model platform. (1st November 2022) - Choi, Hansol; Kim, Dong Hyun; Han, Man Ho; Oh, Hyung-Suk; Heo, Jinseo; Lim, Hyung-Kyu; Choi, Chang Hyuck
Highlights: MeNC catalysts (Me = Cr, Mn, Fe, Co, Ni) with abundant Me-N4 sites were prepared. In experiments, hydrogen evolution reaction (HER) on MeNCs was measured. In theoretical works, hydrogen binding energy (HBE) on Me-N4 sites was predicted. A great correlation was found between the HER activity and HBE except for Ni-N4 . Ni-N3 V1 geometry was identified as the main catalytic site of NiNC. Abstract: NiNC catalysts, in which Ni ions are atomically dispersed by ligation with nitrogen functionalities on a carbon support, have received considerable attention owing to their promising activity in the electrochemical reduction of CO2 to CO. However, a poor catalytic activity has been theoretically predicted for the conventional metalloporphyrin-like catalytic moieties, symmetric Ni-N4 . This has led to extensive debate regarding the nature of the actual catalytic site. In this study, we prepare five MeNC catalysts (Me = Cr, Mn, Fe, Co, or Ni) with predominant Me-N4 moieties and measure their hydrogen evolution reaction (HER) activities. A linear correlation is identified between the HER activity and the theoretically predicted hydrogen binding energy (HBE) of all the symmetric Me-N4 models, except for Ni-N4 . Thus, various coordination structures are further considered as catalytic Ni sites. Based on the combination of experimental and theoretical approaches, we conclude that coordinately unsaturated Ni sites can be present, which are responsible for the considerable electrocatalytic activity of the NiNC. Graphical abstract: Image, graphical abstract